Analysis of Deep‐UV Nonlinear Optical Borates: Approaching the End. Issue 5 (28th February 2014) - Yao, Wenjiao; He, Ran; Wang, Xiaoyang; Lin, Zheshuai; Chen, Chuangtian
<x xml:space="preserve">Abstract</x> The rapid development of deep‐UV (DUV) all‐solid‐state laser sources greatly depends on the good performance of the nonlinear optical (NLO) crystals used for harmonic generation. In this work, the potential prospects for NLO borate crystals are investigated from the point of view of their structure–property relationships. The microscopic structural units, energy bandgaps, linear and nonlinear optical properties of numerous borate compounds with diverse structural features are compared and summarized. The results reveal that KBe2BO3F2 almost achieves the theoretical limits of DUV NLO borates. It would be a great challenge to discover other borates which have comparable NLO capability, especially for coherent light production below the wavelength of 190 nm by direct second harmonic generation.